Driving the Emission Towards Blue by Controlling the HOMO‐LUMO Energy Gap in BF2‐Functionalized 2‐(Imidazo[1, 5‐a]pyridin‐3‐yl)phenols. Issue 48 (12th July 2021) - Colombo, Gioele; Attilio Ardizzoia, G.; Furrer, Julien; Therrien, Bruno; Brenna, Stefano
Abstract: Several boron compounds with 2‐(imidazo[1, 5‐ a ]pyridin‐3‐yl)phenols, differentiated by the nature of the substituent (R) in the para position of the hydroxy group, have been synthesized and thoroughly characterized both in solution ( 1 H, 13 C, 11 B, 19 F NMR) and in the solid state (X‐ray). All derivatives displayed attractive photophysical properties like very high Stokes shift, high fluorescence quantum yields and a good photostability in solution. Time‐Dependent Density Functional Theory (TD‐DFT) calculations allowed to define the main electronic transitions as intra ligand transitions ( 1 ILT), which was corroborated by the Natural Transition Orbitals (NTOs) shapes. The HOMO‐LUMO energy gap was correlated to the electronic properties of the substituent R on the phenolic ring, as quantified by its σp Hammett constant. Abstract : Blue emissive materials : boron containing fluorescent compounds have been prepared starting from imidazo[1, 5‐ a ]pyridine phenols. Large Stokes shift, high absolute quantum yields and good photostability are observed in solution. TD‐DFT calculations allowed to find a linear correlation between the HOMO‐LUMO energy gap of these compounds and the Hammett constants of substituents R para to the hydroxyl group of the phenols.